Role of CT angiography and therapeutic anticoagulation in patients presenting to the emergency department with acute gastrointestinal bleeding. Issue 1 (8th April 2022) - Newman, Chris; Nandurkar, Rohan; Holcdorf, David; Gerstenmaier, Jan; Tagkalidis, Peter; Clements, Warren
Abstract: Introduction: Acute gastrointestinal bleeding (GIB) is associated with morbidity and mortality. There can be a low threshold for practitioners to assess for active GIB and computed tomography angiography (CTA) examinations are performed frequently, even for stable patients and those who are therapeutically anticoagulated. We aimed to assess the predictive value of CTA for acute GIB and the influence of CTA on treatment. Methods: Retrospective single‐centre study over a 2‐year period. Results: A total of 227 patients with mean age 67.7 years (SD 17.86), 58.6% male. 84.4% were for lower GIB. 49 patients were on therapeutic anticoagulation (21.6%). 45 CTAs were positive (19.8%). 22 patients received embolisation, and 15 received acute endoscopic treatment. CTA sensitivity was 68.6% and specificity 89.1%. The PPV was 53.3% and NPV 93.9%. The odds ratio of a positive CTA requiring treatment for patients on therapeutic anticoagulation was 1.1 ( P = 0.932) compared with the odds of patients not taking therapeutic anticoagulation 21.5 ( P < 0.001). The risk ratio for requiring treatment if not taking anticoagulation was 6.2. A total of 19 patients (9.1%) met the definition of CI‐AKI as a result of the CTA. A pre‐existing eGFR of less than 20 was associated with significantly increased odds of developing CI‐AKI (OR 3.95, P = 0.031, 95%CI 1.135–13.782). Conclusions: The presence of anticoagulation has a significant impact on the decision not to perform interventional treatments on patients with acute GIB when CTA is positive. Anticoagulant reversal and volume resuscitation are important front‐line measures, and CTA may have a role for those anticoagulated who are haemodynamically unstable after resuscitation.